Lexical-Semantic Classification of Neologisms in Media Discourse - Sharipova, Sabohat (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Neologisms enhance and enrich any language, but also provide challenges for us until the notions become known and understandable. A neologism dictionary can help us grasp and translate new terms accurately. If the text contains a neologism that is not defined in a dictionary, we must decide its meaning independently, taking into consideration the derived aspects of the provided word and depending on the context. This article describes and illustrates the meaning of neologisms in our language today, their structure and composition, and their lexical-semantic classifications in media discourse.